Flora fanerogâmica da Serra Negra, Minas Gerais, Brasil - Salimena, Fátima Regina Gonçalves; Matozinhos, Carolina Nazareth; Abreu, Narjara Lopes de; Ribeiro, José Hugo Campos; Souza, Filipe Soares de; Menini Neto, Luiz (Rodriguésia, 2013)
The present study aims to characterize the phanerogamic flora of the region of Serra Negra, located in the southern of Zona da Mata of Minas Gerais, between the municipalities of Lima Duarte, Rio Preto, Santa Bárbara do Monte Verde and Olaria. Although this region is considered of high biological importance, it has no previous record of floristic data, which led to the development of this survey, during the period 2003 to 2010. The vegetation is characterized by a mosaic of forests and grassland, especially cloud forests and "campos rupestres" (rocky grasslands), occurring at altitudes between 1300 to 1700 m. A total of 1033 species was recorded, distributed in 469 genera and 121 families. The most representative families are Orchidaceae (115 spp.), Asteraceae 54 spp.), Melastomataceae (56 spp.), Myrtaceae (53 spp.), Fabaceae, Poaceae e Rubiaceae (48 spp. cada), Bromeliaceae (43 spp.), Solanaceae (38 spp.) and Piperaceae (33 spp). New records and endemic species to flora of Minas Gerais were found and 58 species are cited in the list of endangered species of Minas Gerais. O presente estudo teve como objetivo caracterizar a flora fanerogâmica da região da Serra Negra localizada no sul da Zona da Mata de Minas Gerais, entre os municípios de Lima Duarte, Rio Preto, Santa Bárbara do Monte Verde e Olaria. Embora considerada de importância biológica alta, esta região não possui nenhum registro anterior de dados florísticos, o que levou ao desenvolvimento deste levantamento, durante o período de 2003 a 2010. A vegetação é caracterizada por um mosaico de formações florestais e campestres onde se destacam os campos rupestres e florestas nebulares em altitudes que variam de 1300 a ca. 1700 m. Um total de 1033 espécies foi encontrado, distribuídas em 469 gêneros e 121 famílias sendo as mais representativas Orchidaceae (115 spp.), Asteraceae 54 spp.), Melastomataceae (56 spp.), Myrtaceae (53 spp.), Fabaceae, Poaceae e Rubiaceae (48 spp. cada), Bromeliaceae (43 spp.), Solanaceae (38 spp.) e Piperaceae (33 spp). Novos ...